Predicting the development of normal tension glaucoma and related risk factors in normal tension glaucoma suspects - Hae-Young Lopilly Park (Nature Portfolio, 2021)
Abstract This study investigated the predicted risk factors for the development of normal-tension glaucoma (NTG) in NTG suspects. A total of 684 eyes of 379 NTG suspects who were followed-up for at least 5 years were included in the study. NTG suspects were those having (1) intraocular pressure within normal range, (2) suspicious optic disc (neuroretinal rim thinning) or enlarged cup-to-disc ratio (≥ 0.6), but without definite localized retinal nerve fiber layer (RNFL) defects on red-free disc/fundus photographs, and (3) normal visual field (VF). Demographic, systemic, and ocular characteristics were determined at the time of the first visit via detailed history-taking and examination of past medical records. Various ocular parameters were assess using spectral-domain optical coherence tomography and Heidelberg retinal tomography. Conversion to NTG was defined either by the presence of a new localized RNFL defect at the superotemporal or inferotemporal region on disc/fundus red-free photographs, or presence of a glaucomatous VF defect on pattern standard deviation plots on two consecutive tests. Hazard ratios were calculated with the Cox proportional hazard model. In total, 86 (12.6%) of the 684 NTG suspects converted to NTG during the follow-up period of 69.39 ± 7.77 months. Significant (P < 0.05, Cox regression) risk factors included medication for systemic hypertension, longer axial length, worse baseline VF parameters, thinner baseline peripapillary RNFL, greater disc torsion, and lamina cribrosa (LC) thickness < 180.5 μm (using a cut-off value obtained by regression analysis). Significant (P < 0.05, Cox regression) risk factors in the non-myopic NTG suspects included medication for systemic hypertension and a LC thinner than the cut-off value. Significant (P < 0.05, Cox regression) risk factors in the myopic NTG suspects included greater disc torsion. The results indicated that 12.6% of NTG suspects converted to NTG during the 5–6-year follow-up period. NTG suspects taking medication for systemic hypertension, disc torsion of the optic disc in the inferotemporal direction, and thinner LC of the optic nerve head at baseline were at greater risk of NTG conversion. Related baseline risk factors were different between myopic and non-myopic NTG suspects.